Hydropic Ear Disease: Correlation Between Audiovestibular Symptoms, Endolymphatic Hydrops and Blood-Labyrinth Barrier Impairment - de Pont, Lisa M. H.; van Steekelenburg, Josephine M.; Verhagen, Thijs O.; Houben, Maartje; Goeman, Jelle J.; Verbist, Berit M.; van Buchem, Mark A.; Bommeljé, Claire C.; Blom, Henk M.; Hammer, Sebastiaan (Frontiers in Surgery, 2021)
Research Objective: To investigate the correlation between clinical features and MRI-confirmed endolymphatic hydrops (EH) and blood-labyrinth barrier (BLB) impairment. Study Design: Retrospective cross-sectional study. Setting: Vertigo referral center (Haga Teaching Hospital, The Hague, the Netherlands). Methods: We retrospectively analyzed all patients that underwent 4 h-delayed Gd-enhanced 3D FLAIR MRI at our institution from February 2017 to March 2019. Perilymphatic enhancement and the degree of cochlear and vestibular hydrops were assessed. The signal intensity ratio (SIR) was calculated by region of interest analysis. Correlations between MRI findings and clinical features were evaluated. Results: Two hundred and fifteen patients with MRI-proven endolymphatic hydrops (EH) were included (179 unilateral, 36 bilateral) with a mean age of 55.9 yrs and median disease duration of 4.3 yrs. Hydrops grade is significantly correlated with disease duration (P < 0.001), the severity of low- and high-frequency hearing loss (both P < 0.001), and the incidence of drop attacks (P = 0.001). Visually increased perilymphatic enhancement was present in 157 (87.7%) subjects with unilateral EH. SIR increases in correlation with hydrops grade (P < 0.001), but is not significantly correlated with the low or high Fletcher index (P = 0.344 and P = 0.178 respectively). No significant differences were found between the degree of EH or BLB impairment and vertigo, tinnitus or aural fullness. Conclusion: The degree of EH positively correlates with disease duration, hearing loss and the incidence of drop attacks. The BLB is impaired in association with EH grade, but without clear contribution to the severity of audiovestibular symptoms.